Sociologija slovenske literature - Kos, Janko (Primerjalna književnost, 2012)
This article studies the theoretical premises and methodological principles for developing the sociology of Slovenian literature as a systematic scholarly discipline. It complements the empirical sociological analysis model with a socio-historical explanation of ideological elements in literary works, which demands the introduction of more fundamental concepts. Among these, the pair "society" and "community" is important for explaining the specific character and development of Slovenian literature. Slovenian literary sociology can exist only as historical sociology. Its methods must notonly be quantitatively empirical, but also qualitatively interpretative.
Keywords: družba; society; Slovene literature; slovenska književnost; sociologija; sociology; literarna distribucija; literarna recepcija; avtor; skupnost; ideologija; nacionalna identiteta